STRATEGIES OF IMPOLITENESS IN THE KEEPING UP WITH THE KARDASHIANS SERIES ON YOUTUBE - Nadha Jelang Ramdhany; Ambalegin, Ambalegin (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2023)
The primary goal of this descriptive qualitative study was to investigate the strategies of impoliteness used by the speakers in the Keeping Up With The Kardashians series on YouTube. The utterances which contain the strategies of impoliteness uttered by the speakers within the series were taken as the data. Furthermore, the data were analyzed by identifying the impoliteness strategy according to Culpeper (2005)’s theory. Descriptive qualitative by Creswell & Creswell (2018) was performed in this research. The observational method was used as the method to collect the data. Furthermore, to analyze the data pragmatic identity method was conducted along with equalizing technique. The results showed at least fifteen utterances produced by the speakers with an impoliteness strategy in the three videos of the Keeping Up With The Kardashians series. The four (4) data showed negative impoliteness, four (4) data showed sarcasm / mock politeness, three (3) data showed withhold politeness, two (2) data showed bald on record, and two (2) data showed positive impoliteness. The negative impoliteness was the most frequently used by the speakers in the Keeping Up With The Kardashians series. Impoliteness is not always performed by rude behaviors but a simple utterance can also indicate the act of impoliteness.